Analysis of Location Aided Routing Protocols for MANETs: A Literature Survey - Prasad, Ajay; Gautam, Kiran (International Journal of Computer Sciences and Engineering, 2015)
A Mobile Ad-hoc Network (MANET) consists of wireless hosts that may have various degree of mobility. Movement of hosts resulting in a change of topology which require some mechanism establishing the fresh route through mobile nodes and also determining new routes in case of failures. Several routing protocol based on routing information update mechanism, use of temporal information, routing topology, and utilization of specific resources. Proactive and reactive routing protocols have already been proposed based on routing information update mechanism for Ad-hoc networks. Location Aided Routing (LAR) can be classified as the routing protocol based on specific resources like Global Positioning System. LAR is a routing mechanism which attempts to reduce the control message overhead of Ad-hoc on demand distance vector(AODV) routing protocol by flooding only the portion of the network that is likely to contain the route to destination. LAR takes the advantage of resource like GPS coordinates to identify a possible location of the destination node. Based on this information, LAR defines a portion of the network which called a request zone which will be subject to the limited flooding, thus reducing the total number of the control packet travelling through the network during the route discovery process. LAR-I algorithm, which determine the request zone and the expected zone in the process of route discovery. The significant communication overhead can be avoided if the routing strategy is changed. Different strategy of request zone can be used for that in Location Aided Routing e.g., Triangle and Rectangle request zone. Performance of MANET widely depends on the node mobility which was important parameter.